Från orsak till mening – att kunna relatera ritualer till centrala tankegångar inom olika religioner - Frisk, Anna-Karin (Forskning om undervisning och lärande, 2016)
Studien undersöker vad det innebär att kunna relatera rituella handlingar till centrala tankegångar i olika religioner, vilket är ett krav som kursplanen i religionskunskap för år 4-6 har på elevernas kunnande. Resultatet visar att kunnandet kan ses på olika sätt: som att förklara handlingar utifrån centrala tankegångar, eller som att se att centrala tankegångar ger handlingar mening. En slutsats är att en förmåga att se symbolik i handlingar kan vara en ämnesspecifik förmåga som religionskunskapsämnet kan bidra till att utveckla. I diskussionen problematiseras kursplaneformuleringen ”kunskaper om religioner” i anslutning till detta kunnande. Resultatet diskuteras vidare i relation till kunskap och bildning samt ’religious literacy’. Data utgörs av transkriberade elevsamtal, lärarsamtal samt videodokumentation under en Learning study i år 6. From causality to meaning - relating rituals to central ideas in different religions This study aims at finding out what it means to be able to relate ritual actions to central ideas in different religions, which is a requirement stated in the Swedish Religous Education curriculum for grade 4 to 6. It. Results show that the ’knowing’ can be seen in two ways: as an ability to explain ritual actions from central ideas, or to see that the central ideas give meaning to ritual actions. A conclusion from the results in this study is that an ability to see symbolism in actions can be a subject-specific ability that religious studies could help develop. A discussion relating to knowledge, formation and religious literacy is held. The results further suggest that the Religious Education curriculum needs to be problematized in relation to the phrase ‘knowledge of religions’, as well as to how to develop the specified knowing. Data consists of transcribed records from sound recordings and videodocumentation during a Learning Study in grade 6.